Terrestrial formation of calcium sulfate and carbonate assemblages in Atacama CO chondrites: Implications for Martian evaporitic environments - Gabriel A. Pinto; Vinciane Debaille; Jolantha Eschrig; Alexandre Corgne; Kevin Soto; Thierry Leduc; Sophie Decree; Steven Goderis (Icarus, 2026)

Trace element partitioning during water-saturated eclogite melting at 3 GPa under variable oxygen fugacity – Implications for subduction zone magmatism - Alexandre Corgne; Gaëlle Plissart; Julien Siebert; Jessica Langlade; Christèle Guivel; José Joaquín Figueroa Ruíz; Joaquín Catalan; Manuel Enrique Schilling (Geochimica et Cosmochimica Acta, 2026)

Origin and stabilization of off-craton continental lithosphere recorded by cratonic mantle relics in Pali-Aike (southern Patagonia) - Erwin Schettino; Claudio Marchesi; Max W. Schmidt; José María González‑Jiménez; Alexandre Corgne; Manuel E. Schilling (Earth and Planetary Science Letters, 2026)

Birth, life and death of the Devonian Chaitenia back-arc along the Southwestern Gondwanan margin (southern Chile) - Gaëlle Plissart; Juan Carlos Moral Yilorm; José María González-Jiménez; Jesús Muñoz-Montecinos; Carolina Pavez Salgado; Aníbal Rivera Herrera; Fiona Cabrera Bermúdez; Claudio Marchesi; Alexandre Corgne; Antonio Jesús Moreno Abril; Pierre Lanari; Julien Berger; et al. (Gondwana Research, 2026)

Micron-to-nanoscale investigation of Cu-Fe-Ni sulfide inclusions within laurite (Ru, Os)S2 from chromitites - José María González-Jiménez; Igor González-Pérez; Gaëlle Plissart; Amira R. Ferreira; Erwin Schettino; Lola Yesares; Manuel E. Schilling; Alexandre Corgne; Fernando Gervilla (Mineralium Deposita, 2025)
This paper provides a top-down nanoscale analysis of Cu-Ni-Fe sulfide inclusions in laurite from the Taitao ophiolite (Chile) and the Kevitsa mafic-ultramafic igneous intrusion (Finland). High-resolution transmission electron microscopy (HRTEM) reveal that Cu-Ni-Fe sulfide inclusions are euhedral to (sub)-anhedral (i.e., droplet-like) and form single, biphasic or polyphasic grains, made up of different polymorphs, polytypes and polysomes even within a single sulfide crystal. Tetragonal (I4 $$\stackrel{-}{2}$$ d) and cubic (F $$\stackrel{-}{4}$$ 3m) chalcopyrite (CuFeS 2 ) host frequent fringes of bornite (Cu 5 FeS 4 ; cubic F $$\stackrel{-}{4}$$ 3m and/or orthorhombic Pbca) ± talnakhite (Cu 9 (Fe, Ni) 8 S 16 ; cubic I $$\stackrel{-}{4}$$ 3m) ± pyrrhotite (Fe 1 − x S; monoclinic C2/c polytype 4C and orthorhombic Cmca polytype 11C) ± pentlandite ((Ni, Fe) 9 S 8 ; cubic Fm3m). Pentlandite hosts fringes of pyrrhotite, bornite and/or talnakhite. Laurite and Cu-Fe-Ni sulfide inclusions display coherent, semi-coherent and incoherent crystallographic orientation relationships (COR), defined by perfect edge-to-edge matching, as well as slight (2–4º) to significant (45º) lattice misfit. These COR suggest diverse mechanisms of crystal growth of Cu-Fe-Ni sulfide melt mechanically trapped by growing laurite. Meanwhile, the mutual COR within the sulfide inclusions discloses: (1) Fe-Ni-S melt solidified into MSS re-equilibrated after cooling into pyrrhotite ± pentlandite, (2) Cu-Ni-Fe-S melts crystallized into the quaternary solid solution spanning the compositional range between heazlewoodite [(Ni, Fe) 3±x S 2 ] (Hz ss ) and ISS [(Cu 1±x , Fe 1±y )S 2 ]. Additionally, nanocrystallites (50–100 nm) of Pt-S and iridarsenite (IrAsS) accompanying the sulfide inclusions spotlight the segregation of PGE-rich sulfide and arsenide melt earlier and/or contemporarily to laurite crystallization from the silicate magmas. Cobaltite (CoAsS)-gersdorffite (NiAsS) epitaxially overgrown on laurite further supports the segregation of arsenide melts at early stages of chromitite formation.

Local controls on magma fertility in the Mio-Pliocene metallogenic belt of central Chile: Exploration implications - Jose Piquer; Jorge Torres; Matías González; Amanda Valdés; Bárbara González; Alexandre Corgne (Journal of South American Earth Sciences, 2024)

Deciphering recycling processes during solar system evolution from magnesium-rich relict olivine grains in type II chondrules - Gabriel A. Pinto; Emmanuel Jacquet; Alexandre Corgne; Felipe Olivares; Johan Villeneuve; Yves Marrocchi (Geochimica et Cosmochimica Acta, 2024)

Titanium Dioxide Nanoparticles Increase Tissue Ti Concentration and Activate Antioxidants in Solanum lycopersicum L. - Ricardo Tighe-Neira; Marjorie Reyes-Díaz; Adriano Nunes-Nesi; Gonzalo Recio; Erico R. Carmona; Ricard Marcos; Alexandre Corgne; Zed Rengel; Claudio Inostroza-Blancheteau (Journal of Soil Science and Plant Nutrition, 2021)

Magmatic platinum nanoparticles in metasomatic silicate glasses and sulfides from Patagonian mantle xenoliths - José María González-Jiménez; Josep Roqué-Rosell; Abigail Jiménez-Franco; Santiago Tassara; Fernando Nieto; Fernando Gervilla; Sandra Baurier; Joaquín A. Proenza; Edward Saunders; Artur P. Deditius; Manuel Schilling; Alexandre Corgne (Contributions to Mineralogy and Petrology, 2019)

Trace element partitioning and substitution mechanisms in calcium perovskites - Alexandre Corgne; Bernard J. Wood (Contributions to Mineralogy and Petrology, 2005)

Compositional effects on element partitioning between Mg-silicate perovskite and silicate melts - Christian Liebske; Alexandre Corgne; Daniel J. Frost; David C. Rubie; Bernard J. Wood (Contributions to Mineralogy and Petrology, 2005)

An experimental study of element partitioning between magnetite, clinopyroxene and iron-bearing silicate liquids with particular emphasis on vanadium - Michael J. Toplis; Alexandre Corgne (Contributions to Mineralogy and Petrology, 2002)